Characterization of Cement Treated Crushed Rock for Western Australia Road - Jitsangiam, Peerapong; Nikraz, Hamid; Siripun, K. (Kasetsart University, 2009)
Hydrated Cement Treated Crushed Rock Base (HCTCRB) is widely used as a base course material for Western Australian roads. HCTCRB has been designed and used based on an empirical approach and practical experience, respectively, but those are not capable of explaining behavior of HCTCRB. Presently, a mechanistic approach is considered more reliable in pavement design and analysis. Mechanistic methods also provide effective tools in better understanding of pavement performance. The study provides laboratory testing and the corresponding analysis so as to assess the mechanical characteristics of HCTCRB. Conventional triaxial tests and repeated load triaxial tests (RLT tests) were performed. Factors, which would affect the performance of HCTCRB such as hydration periods and the amount of added water, were also investigated.